The art world of Club Beethoven in Rio de Janeiro at the end of 19th century - Velasco, Joyce Veiga (Revista do Colóquio, 2024)
At the end of the 19th century, there was a rise in musical associations in Rio de Janeiro, including the Club Beethoven. Within this institution, chamber music was one kind of the concerts offered, and string quartets became a constant feature. This study examines the institutional aspects of the Club Beethoven, the role of the string quartet musicians, the repertoire performed, and the musicians' remuneration, by using Howard Becker's methodology, which advocates for addressing historical gaps, aiming for a more comprehensive understanding of chamber music practice in Rio de Janeiro during this period.